Gap soliton transparency switching and defect mode formation in one-dimensional Kerr-metamaterial superlattices and strips - Lobo, Tiago Peixoto da Silva (2017)
Plasmon-polariton gap soliton formation and transparency switching in one-dimensional nonlinear layered systems composed of alternate layers of a Kerr material and a dispersive linear metamaterial are theoretically studied. The behavior of the electric field profile inside the layered system is shown for different values of nonlinear power, linking the localized modes of the electric field with complete transparency states of the system. A detailed investigation on the influence of a defocusing nonlinearity on the transmission switching phenomenon, in the frequency range where the linear dispersion predicts the photon-plasmon coupling, is made, revealing different effects in the top and bottom edges of the plasmon-polariton gap. Specifically, we found a broadening of the plasmon-polariton gap when increasing the nonlinear power. In addition, a switching from very low to high transmission states is obtained and localized plasmon-polariton gap solitons of various orders are found for various values of frequencies and nonlinear strength. Defect modes in a reduced lattice composed of a regular material sandwiched by a bilayer Kerr/dispersive metamaterial are also studied. The behavior of the electric profile inside the strips is studied for varying defect layer size and for an increasing focusing nonlinearity, linking each transparency point to a defect mode. In addition, the transmission function is found to be periodic in the linear regime and this periodicity is not affected by a focusing nonlinearity. Furthermore, each defect mode is linked to a n-peak electric field profile and a well defined parity. By choosing consecutive defect modes we have shown that the parity is switched and the electric field profile gets a new peak added to it, in the linear regime. Moreover, by fixing a defect layer size and studying the effects of an increasing focusing nonlinearity we found multistability, hysteresis and observed parity switch and new peaks being added to the electric profile as one chooses consecutive transparency points.